2022
DOI: 10.1021/acschembio.2c00626
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Allosteric Binding Site for Thiazolopyrimidine on the C-Type Lectin Langerin

Abstract: Langerin is a mammalian C-type lectin expressed on Langerhans cells in the skin. As an innate immune cell receptor, Langerin is involved in coordinating innate and adaptive immune responses against various incoming threats. We have previously reported a series of thiazolopyrimidines as murine Langerin ligands. Prompted by the observation that its human homologue exhibits different binding specificities for these small molecules, we report here our investigations to define their exact binding site. By using str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Indeed, recent works have targeted a site near the long loop for the C-type lectin receptor Langerin. 70,71…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, recent works have targeted a site near the long loop for the C-type lectin receptor Langerin. 70,71…”
Section: Resultsmentioning
confidence: 99%
“…38A and B ). 584 Whether the inhibition mechanism of the thiazolopyrimidines is based on the interference with the long loop, similar to what has been observed for E-selectin, covering the central fucose, remains to be elucidated. Interestingly, this cleft between the long and the short loop was previously reported to harbour a short peptide, suggesting it is amenable to modulation via small molecule inhibitors.…”
Section: Novel Glycomimetic Scaffolds For Ca 2+ -D...mentioning
confidence: 93%
“… 161 In recent follow-up on this work, the binding site for this compound class was determined using NMR and computational methods. 584 The allosteric site of langerin is located in the cleft between the long and short loop, the so-called bridging region ( Fig. 38 ).…”
Section: Novel Glycomimetic Scaffolds For Ca 2+ -D...mentioning
confidence: 99%
“…Likewise, high‐throughput screenings (HTS) yielded biologically active and chemically tractable lead structures [89,129–131] . Follow‐up studies and mode of action analysis suggested some of these secondary sites to impact CLR function via unprecedented mechanisms, including allosteric modulation of the canonical CBS and changes in quaternary conformation [13,89,130–135] . For instance, a recently identified small molecule ligand was shown to inhibit LOX‐1‐dependent oxLDL uptake by cross‐linking two dimers in a head‐to‐head fashion, sterically blocking the basic spine region, and locking the receptor in an inactive tetramer state (Figure 3c, d and e).…”
Section: Secondary Sitesmentioning
confidence: 99%
“…[89,[129][130][131] Follow-up studies and mode of action analysis suggested some of these secondary sites to impact CLR function via unprecedented mechanisms, including allosteric modulation of the canonical CBS and changes in quaternary conformation. [13,89,[130][131][132][133][134][135] For instance, a recently identified small molecule ligand was shown to inhibit LOX-1-dependent oxLDL uptake by cross-linking two dimers in a head-to-head fashion, sterically blocking the basic spine region, and locking the receptor in an inactive tetramer state (Figure 3c, d and e). [89] Consequently, apart from their biological role, secondary sites have become increasingly relevant in the context of CTLtargeted drug discovery.…”
Section: Secondary Sitesmentioning
confidence: 99%